2021
DOI: 10.1097/hcr.0000000000000577
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Impact of Masking Is Insignificant and Should Not Preclude Routine Use During Daily Activities, Exercise, and Rehabilitation

Abstract: With the outbreak of SARS-CoV-2, mandatory public masking has been broadly implemented. However, the perceived impact of mask use on pulmonary function is a deterrent to public compliance. In this report, we review the impact of masks on pulmonary function and provide recommendations for masking during exercise and rehabilitation during COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 36 publications
(33 reference statements)
0
43
0
Order By: Relevance
“…Our findings are supported by multiple previous studies; however, no adverse physiological effects or risk of face mask use during exercise were reported. 14,17,18,32,33 Therefore, overall breathing comfort should be used to guide type of face masks when exercising in the heat.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are supported by multiple previous studies; however, no adverse physiological effects or risk of face mask use during exercise were reported. 14,17,18,32,33 Therefore, overall breathing comfort should be used to guide type of face masks when exercising in the heat.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the surgical mask was placed loosely on top of the oxygenation device to limit the effect on the work of breathing. 39 Thus, the primary objective is to deflect the exhalation puffs, rather than to filter them as in the N95 mask. From these side-by-side images, and the associated movies in Figs.…”
Section: Exhaled Puff Redirection With Surgical Mask Covermentioning
confidence: 99%
“…The question arises, however, whether different types of face masks have negative effects on ventilation, cardiovascular function and metabolism. This issue has been addressed in publications that have measured the effects of different types of face mask on hemodynamic, cardiopulmonary, and metabolic parameters during exercise (17,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Some studies found that wearing a face mask during exercise reduced cardiopulmonary function or exercise performance (7,23,26,27).…”
Section: Introductionmentioning
confidence: 99%